Analytical techniques for multiplex analysis of protein biomarkers. (2nd April 2020) - Van Gool, Alain; Corrales, Fernado; Čolović, Mirjana; Krstić, Danijela; Oliver-Martos, Begona; Martínez-Cáceres, Eva; Jakasa, Ivone; Gajski, Goran; Brun, Virginie; Kyriacou, Kyriacos; Burzynska-Pedziwiatr, Izabela; Wozniak, Lucyna Alicja; et al.
ABSTRACT: Introduction: The importance of biomarkers for pharmaceutical drug development and clinical diagnostics is more significant than ever in the current shift toward personalized medicine. Biomarkers have taken a central position either as companion markers to support drug development and patient selection, or as indicators aiming to detect the earliest perturbations indicative of disease, minimizing therapeutic intervention or even enabling disease reversal. Protein biomarkers are of particular interest given their central role in biochemical pathways. Hence, capabilities to analyze multiple protein biomarkers in one assay are highly interesting for biomedical research. Areas covered: We here review multiple methods that are suitable for robust, high throughput, standardized, and affordable analysis of protein biomarkers in a multiplex format. We describe innovative developments in immunoassays, the vanguard of methods in clinical laboratories, and mass spectrometry, increasingly implemented for protein biomarker analysis. Moreover, emerging techniques are discussed with potentially improved protein capture, separation, and detection that will further boost multiplex analyses. Expert commentary: The development of clinically applied multiplex protein biomarker assays is essential as multi-protein signatures provide more comprehensive information about biological systems than single biomarkers, leading to improved insights in mechanisms of disease, diagnostics, and the effect of personalized medicine.